2021
DOI: 10.3390/jmse9020164
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Motion Behavior and Longitudinal Stability Assessment of a Trimaran Planing Hull Model in Calm Water

Abstract: In this study, a high-speed planing trimaran hull form is designed, and the effects of different displacements and gravity longitudinal layouts on the performance of the trimaran planing hull in calm water are experimentally investigated in the towing tank of the China Special Vehicle Research Institute. Based on previous work, an innovative inner tunnel appendage hydroflap is mounted in the inner aft tunnel, located 1/8 L from the transom in the longitudinal direction with attack angles of 0° and 4°, respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…In the early research, wind tunnel model test has become the main method to study the stability of the ultra-high-speed aerodynamically alleviated marine vehicle [1,2]. Zou et al studied the effects of displacement and gravity longitudinal layouts on the performance of an aerodynamically alleviated trimaran in calm water by model towing test, and results show that moving the gravity center forward and increasing the mass can improve the longitudinal stability, which results in a higher resistance cost in the high-speed region [3]. Wang carried out the study of the WIG craft experimentally based on the moving wavy ground test, and found that the longitudinal characteristics of the vehicle were affected by the wave height and the wave height change rate [4].…”
Section: Introductionmentioning
confidence: 99%
“…In the early research, wind tunnel model test has become the main method to study the stability of the ultra-high-speed aerodynamically alleviated marine vehicle [1,2]. Zou et al studied the effects of displacement and gravity longitudinal layouts on the performance of an aerodynamically alleviated trimaran in calm water by model towing test, and results show that moving the gravity center forward and increasing the mass can improve the longitudinal stability, which results in a higher resistance cost in the high-speed region [3]. Wang carried out the study of the WIG craft experimentally based on the moving wavy ground test, and found that the longitudinal characteristics of the vehicle were affected by the wave height and the wave height change rate [4].…”
Section: Introductionmentioning
confidence: 99%